Using «Discrete Mathematics» site as an educational resource in terms of personal based learning - Медведєва, Марія Олександрівна (Pedagogy of Higher and Secondary Education, 2015)
Medvedyeva M. O. Using «Discrete Mathematics» site as an educational resource in terms of personal based learning. In the article the relevance and usefulness of educational resource «Discrete Mathematics», used for the person centered education of Discrete Mathematics with the aids of information technology in higher educational institution are analysed. The technology used to create the site wre described.